Anthrax Toxin Detection: From In Vivo Studies to Diagnostic Applications - Jean-Nicolas Tournier; Clémence Rougeaux (Microorganisms, 2020)
Anthrax toxins are produced by Bacillus anthracis throughout infection and shape the physiopathogenesis of the disease. They are produced in low quantities but are highly efficient. They have thus been long ignored, but recent biochemical methods have improved our knowledge in animal models. This article reviews the various methods that have been used and how they could be applied to clinical diagnosis.